STRUCTURAL AND FUNCTIONAL PECULIARITIES OF INTRODUCTORY CONSTRUCTIONS IN UKRAINIAN SCIENTIFIC DISCOURSE - Novikova, O. (Studia Philologica, 2020)
Scientific style is one of the functional styles, which is now actively and dynamically developing. It aims to reflect the phenomena of linguistic reality and the processes of the society modern development. The mandatory features of the scientific texts syntax can be completed to the abstractivness and generalization, which are manifested as the exception of a personal subject of action (deagency) from the sentence structure and the wide applicability of nominalizing structures (the nominal nature of a statement). One of the ways to implement the deagency and nominal nature of a statement of scientific thought is the use of introductory constructions. Activation of introductory units in modern Ukrainian scientific speech is an innovative phenomenon. They have different extralinguistic nature and perform tasks that implement various communication patterns. The use of introductory constructions in a scientific text is necessary not only for the expressiveness of the message, but also for semantic integrity, which is ensured by combining all parts of the text around one topic. They help to realize such categories of the text as coherence, modality, consistency, and articulation. The specificity of the choice of introductory units depends on author's individual style, his thoughts about a particular problem, and predetermines the choice of linguistic means for conducting scientific discussion or argumentation. The article traces new trends in the communicative and pragmatic organization of modern Ukrainian scientific discourse due to the use of various types of introductory constructions. Their main functions and stylistic manifestations within the most important semantic groups are identified; the ways of structural and grammatical, and functional and stylistic diversity of introductory words, word combinations and sentences are established. Analyzing the actual material regarding the use of introductory words, phrases and sentences in modern Ukrainian scientific discourse, we state that they acquire a wider use and stylistic weight, serve as a means of implementing several communicative and pragmatic functions: text and connectedness, accent and affirmative, accent and hypothetical, and appraisal functions. There is a noticeable tendency towards the predominant use of the Ukrainian proper introductory words, phrases and sentences, which are increasingly confidently squeezing out of use common early introductory units, which testifies to the Ukrainization of scientific speech. Key words: introductory constructions, functions, semantic group, stylistic manifestation, modern Ukrainian scientific discourse.